2009
DOI: 10.1093/europace/eup350
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of silent cerebral embolism during pulmonary vein catheter ablation for atrial fibrillation

Abstract: This study shows a high incidence of silent micro-embolic events after PV ablation. CAD, left ventricular dilatation, and hypertrophy were potential predictors of this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 31 publications
1
88
3
Order By: Relevance
“…A recent update of their observational cohort study indicated ischemic lesions in 11.3% patients, whereas physical examination revealed a transient reflex abnormality in 1 patient. 22 The presently largest prospective MRI study reported 1 (0.4%) periprocedural TIA and new brain lesions in 33 (14.2%) out of 232 LACA patients without apparent neurological deficits. 23 Smaller nonrandomized MRI studies reported acute brain lesions in 7.9% to 9.5% of all patients after LACA using radiofrequency or cryoenergy.…”
Section: Laca-associated Strokementioning
confidence: 93%
See 2 more Smart Citations
“…A recent update of their observational cohort study indicated ischemic lesions in 11.3% patients, whereas physical examination revealed a transient reflex abnormality in 1 patient. 22 The presently largest prospective MRI study reported 1 (0.4%) periprocedural TIA and new brain lesions in 33 (14.2%) out of 232 LACA patients without apparent neurological deficits. 23 Smaller nonrandomized MRI studies reported acute brain lesions in 7.9% to 9.5% of all patients after LACA using radiofrequency or cryoenergy.…”
Section: Laca-associated Strokementioning
confidence: 93%
“…19,20 In addition to these clinically apparent ischemic strokes, brain imaging can identify further cerebral damage in patients after LACA (Table 2), similar to those reported after invasive cardiovascular procedures like diagnostic coronary angiography, carotid endarterectomy, or cardiac surgery. [21][22][23][24][25][26] Lickfett et al were the first to demonstrate the utility of diffusionweighted MRI to detect clinically "silent" strokes after LACA. A recent update of their observational cohort study indicated ischemic lesions in 11.3% patients, whereas physical examination revealed a transient reflex abnormality in 1 patient.…”
Section: Laca-associated Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Although there has been a reduction in procedural thromboembolism events with the use of open-irrigated catheters and heparinization, there is growing evidence for silent cerebral infarcts/ lesions and significant concern regarding the long-term consequences of these, particularly dementia and cognitive decline. [57][58][59] The recognition of shortcomings and complications from RF, which are fundamentally a consequence of thermal heat generation and collateral damage, has seen a growth and desire to find and test alternate energy approaches. In particular, there has been renewed interest in the application of DC energy for ablation.…”
Section: Novel Ablation Modalities On the Horizonmentioning
confidence: 99%
“…This broad variation can be 4 attributed to the different patient characteristics, anticoagulation protocol and type of energy used to perform the ablation among different studies [14][15][16][17] .…”
Section: Cerebral Ischemia and Atrial Fibrillation Ablationmentioning
confidence: 99%